Splendor of India : among the great wonders - Sinha, Rakesh (Gurgaon Shubhi Publications, 2018)
India Splendor includes the best among many monuments and marvels of architecture and design, which our country boasts of. And all of them are wonders themselves. But one has to choose some. The wonder may be defined as something, having some specific features not seen earlier. All wonders have their specific characteristics, which attract visitors. History of Indian architecture and design begins with Indus Valley Civilization. Indian architecture boasts of a wide variety of historical and traditional structures. The diversity of Indian culture is represented in the form of architecture. Indian architecture has glimpses of varied native traditions, blended with building types, forms and technology from Central Asia and Europe. With the establishment of Mughal Empire in 16th century, a sophisticated channel of Indian regional elements was erected. A cornerstone of the architecture, the arch, had first been developed by Indus Valley people and it later became a staple of Indian architecture. In ancient times, Indian style Hindu and Buddhist temples were constructed in foreign countries, such as Cambodia$1 (Bs Angkor Wat, and Java$1 (Bs Prambanan.s
Keywords: Temples; Architecture